Immune response of the bay scallop, Argopecten irradians, after exposure to the algicide palmitoleic acid. (October 2016) - Chi, Cheng; Giri, Sib Sankar; Jun, Jin Woo; Yun, Saekil; Kim, Hyoun Joong; Kim, Sang Guen; Park, Se Chang
Abstract: Palmitoleic acid (PA) is an effective algicide against the toxin-producing dinoflagellate Alexandrium tamarense ; however, its effects on the immune system of the edible bay scallop Argopecten irradians are unclear. Therefore, we investigated the effects of PA on the immune response in A. irradians by assessing total haemocyte counts (THC), alkaline phosphatase activity (ALP), nitrite oxide (NO), glutathione (GSH), and lactate dehydrogenase (LDH) levels, as well as the expression of immune-related genes ( FREP, PGRP, HSP90, MnSOD, and Cu/ZnSOD ) at various hours post-exposure (hpe) to the compound. THC decreased in PA-treated groups, whereas ALP increased significantly in all of the PA treatment groups at 3 hpe, after which it significantly decreased. The LDH and NO levels were significantly enhanced in the high and medium concentration group. Notably, the GSH level increased in all PA treatment groups at each time interval. Our study revealed that after treatment with different concentrations of PA, variable effects on the expression of genes involved in the immune system response were observed. The results of our study demonstrate that immersing scallops in PA at effective concentrations could result in differential effects on immune system responses and expression of immune-related genes. Specifically, PA may disrupt the endocrine system or affect signal transduction pathways in the scallops. Therefore, the present study highlights the potential risk of using the PA as an algicide to control algal bloom outbreaks in the marine environment. Highlights: We investigated the effect of palmitoleic acid on the bay scallop. Immune system of bay scallop was altered by palmitoleic acid. Response of immune function to palmitoleic acid was time and concentration-dependent.